Dry sliding behavior (block-on-ring tests) of AISI 420 martensitic stainless steel, surface hardened by low temperature plasma-assisted carburizing. (November 2016) - Angelini, V.; Boromei, I.; Martini, C.; Scheuer, C.J.; Cardoso, R.P.; Brunatto, S.F.; Ceschini, L.
Abstract: This paper reports on the dry sliding behavior (block-on-ring tests) of Low-Temperature Plasma Carburized (LTPC) AISI 420 martensitic stainless steel, treated under different times (4–16 h) and temperatures (350–500 °C), so as to identify the relationships between microstructure, micro-hardness and tribological behavior. In particular, LTPC was effective in decreasing wear when treatment conditions led to the highest diffusion layer thickness combined with absence of a thick outer layer (i.e. at 450 °C for a treatment time of 12 h). The dominant wear mechanism was mild tribo-oxidation, with the protective oxide tribolayer being partly removed by abrasive debris in samples treated at 500 °C. Highlights: AISI 420 Low Temperature Plasma Carburizing (LTPC) with different time (4–16 h) and temperature (350–500 °C). LTPC produced a diffusion zone, sometimes covered with an outer, thin layer (<5 µm). Dry sliding behavior was related to microstructural features and microhardness. Dominant wear mechanism: mild tribo-oxidative wear. Wear decreases if a thick diffusion layer with no outer layer is produced by LTPC (450 °C, 12 h).